PENGARUH WORK-LIFE BALANCE TERHADAP TURNOVER INTENTION DENGAN EMPLOYE ENGAGEMENT SEBAGAI VARIABEL INTERVENING (STUDI PADA KARYAWAN PO JAYA PONOROGO) - Innes Ardian Novitasari; Robby Sandhi Dessyarti (ITB AAS INDONESIA Surakarta, 2022)
This study uses a quantitative approach with a Structural Equation Modeling (SEM) model using a Partial Least Square (PLS) approach. The study population was all employees of PO JAYA Ponorogo during the study period, amounting to 55 people. Determination of the number of samples using the census method or the saturated sampling technique. The research instrument is a questionnaire that has been tested for validity and reliability. The data analysis technique used the Partial Least Square (PLS) method with SmartPLS version 3.0 software. The results of the study prove that: (1) Work-life balance has no significant effect on turnover intention of PO JAYA Ponorogo employees, (2) Work-life balance has a significant effect on employee engagement in PO JAYA Ponorogo employees, (3) Employee engagement has a significant effect on turnover intention of PO JAYA Ponorogo employees, and (4) Work-life balance has a significant effect on turnover intention of PO JAYA Ponorogo employees through employee engagement as an intervening variable.